Sequential Methods in Statistical Process Monitoring, Chapter 4: Sequential Monitoring of Models, Chapter 5: Summary and Future Research, and Appendix: Table of ARL Values - Ramirez, Jose; Box, George (My University, 1991)
An extension of the cumulative sum charts based on the Fisher's score function is introduced. This CUSCORE can be used to monitor parameter changes in a model. It is shown that the traditional CUSUM for location is a particular case of the CUSCORE.